THE SIGNIFICANCE OF TRADITIONAL ORNAMENTATION IN DEVELOPING STUDENTS’ ARTISTIC SKILLS IN VISUAL ARTS EDUCATION - Raxmonova Mahliyo Zoir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores the pedagogical importance of traditional ornamentation in visual arts education. It examines how incorporating national decorative patterns and motifs into lessons fosters students’ creativity, aesthetic development, and cultural understanding. The paper also discusses strategies for effectively integrating traditional ornamentation into modern art education.